2013
DOI: 10.1002/mus.23730
|View full text |Cite
|
Sign up to set email alerts
|

Myositis with antimitochondrial antibodies diagnosed by rectus abdominis muscle biopsy

Abstract: In myositis patients with antimitochondrial M2 antibodies, muscles of the extremities are involved to a lesser extent. Radiological and histological examination focusing on truncal muscles, including a biopsy, is important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 5 publications
2
12
0
Order By: Relevance
“…c  Representative images in skeletal muscle CT were shown. In the patient with anti-M2 antibody (upper panel) [11], paravertebral muscle was severely atrophied, although quadriceps was nearly intact. In the patient without anti-M2 (lower panel), Mm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…c  Representative images in skeletal muscle CT were shown. In the patient with anti-M2 antibody (upper panel) [11], paravertebral muscle was severely atrophied, although quadriceps was nearly intact. In the patient without anti-M2 (lower panel), Mm.…”
Section: Resultsmentioning
confidence: 99%
“…Inflammation appeared to be more intense in the trunk, rather than in the limbs of the positive group. We previously reported a case of anti-M2 antibody-positive myositis that was un-diagnosed following the initial biopsy of the M. biceps brachii , and required the second biopsy of the rectus abdominis muscle [11]. The underlying reasons for the observed reduced intensity in inflammatory changes in the extremities remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we found that the clinical features in patients with AMAs showed great variability. Firstly, although AMAs only occurred in adult IIM patients, the age at onset ranged from 23 years to 86 years and the mean age at onset ranged from the fourth decade to the seventh decade [3][4][5]7,8,[20][21][22][23][24][25][26] . Besides, the average disease duration varied from 10 months (in our study) to 6.5 years, and the prevalence of chronic disease duration varied from approximately 30% (in our study) to 85% [3,5,6] .…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports of cases diagnosed as a result of atrial fibrillation and the detection of heart failure symptoms,20 and Maeda et al 12 reported that 2 out of 24 (8%) AMA-positive cases of myositis were first detected with arrhythmia. Our patient was hospitalised as a result of an AFL noted on his ECG findings, and he was subsequently diagnosed following an AMA evaluation performed due to mildly abnormal AST/ALT results noted on hospitalisation.…”
Section: Discussionmentioning
confidence: 99%